2019
DOI: 10.1016/j.eswa.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Case-base maintenance of a personalised and adaptive CBR bolus insulin recommender system for type 1 diabetes

Abstract: People with type 1 diabetes must control their blood glucose level through insulin infusion either with several daily injections or with an insulin pump. However, estimating the required insulin dose is not easy. Recommender systems, mainly based on Case-Based Reasoning (CBR), are being developed to provide recommendations to users. These systems are designed to keep the experiences or cases of the user in a case-base, which requires maintenance to keep system's response accurate and efficient. This paper prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Starting with the fully personalized paradigm, we use three representatives: 1) A state-ofthe-art method for estimating Individualized Treatment Effects (ITE) called CFRnet [31]; 2) A state-of-the-art deep-learning model explicitly designed for depression treatment selection called Vulcan [32]; and 3) A classic Case Based Reasoning (CBR) approach [33]. We discuss these representatives next and contrast them with our approach.…”
Section: Related Work In Machine-assisted Treatment Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with the fully personalized paradigm, we use three representatives: 1) A state-ofthe-art method for estimating Individualized Treatment Effects (ITE) called CFRnet [31]; 2) A state-of-the-art deep-learning model explicitly designed for depression treatment selection called Vulcan [32]; and 3) A classic Case Based Reasoning (CBR) approach [33]. We discuss these representatives next and contrast them with our approach.…”
Section: Related Work In Machine-assisted Treatment Selectionmentioning
confidence: 99%
“…Nevertheless, several researchers have investigated RS that utilize the CBR approach for treatment selection (e.g. [33]) which relies on the idea of detecting similarities between patients. These have also been applied for mental health treatment selection [40].…”
Section: Related Work In Machine-assisted Treatment Selectionmentioning
confidence: 99%
“…At present, CBR has been widely used in AI, and it has become a new methodology of problem solving and learning [10]. With the gradual maturity of theories and methods, the applications of CBR have been extended to various fields, including medical treatment [11,12,13,14,15], planning [16,17], assessment [18,19], forecast [20,21], game [22], recommendation system [23], management [24] and so on [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [ 30 ] proposed a CBR to improve the accuracy of breast cancer recurrence prediction, and Bentaiba-Lagrid et al [ 31 ] reported an approach to classify mammography mass and thyroid diseases. Torrent-Fontbona et al [ 32 ] developed a CBR, using a numerical solution as an output rather than predetermined class labels to quantify the bolus insulin dosage. CBR has also been recently used for medical image processing applications, e.g., to improve kidney tumor segmentation as reported by Marie et al [ 33 ].…”
Section: Introductionmentioning
confidence: 99%